2011
DOI: 10.1159/000329825
|View full text |Cite
|
Sign up to set email alerts
|

Differential Hemodynamic Effects of Levosimendan in a Porcine Model of Neonatal Hypoxia-Reoxygenation

Abstract: Background: Neonatal asphyxia can be complicated by myocardial dysfunction with secondary alterations in pulmonary and regional hemodynamics. Levosimendan is a calcium-sensitizing inotrope that may support cardiac output, but little is known regarding its differential hemodynamic effects in asphyxiated neonates. Methods: Mixed breed piglets (1–4 days old, weight 1.6–2.3 kg) were acutely instrumented. Normocapnic alveolar hypoxia (10–15% oxygen) was induced for 2 h, followed by reoxygenation with 100% (1 h) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…Ainsi, le levosimendan semble extrêmement intéressant en cas d'hypertension artérielle pulmonaire persistante du nouveau-né responsable d'insuffisance cardiaque sévère [49]. Sur un modèle porcin d'hypoxie-réoxygénation néonatale (deux heures de fraction inspirée en oxygène (FiO 2 ) entre 10 et 15 %, suivies d'une heure de FiO 2 à 21 %), une dose de 0,2 mg/kg/min permettait une amélioration significative de la fonction cardiaque sans hypotension systémique franche [50].…”
Section: Insuffisance Cardiaque Aiguëunclassified
“…Ainsi, le levosimendan semble extrêmement intéressant en cas d'hypertension artérielle pulmonaire persistante du nouveau-né responsable d'insuffisance cardiaque sévère [49]. Sur un modèle porcin d'hypoxie-réoxygénation néonatale (deux heures de fraction inspirée en oxygène (FiO 2 ) entre 10 et 15 %, suivies d'une heure de FiO 2 à 21 %), une dose de 0,2 mg/kg/min permettait une amélioration significative de la fonction cardiaque sans hypotension systémique franche [50].…”
Section: Insuffisance Cardiaque Aiguëunclassified
“…A small observational study in term infants showed a good response to norepinephrine [19] . Other agents such as milrinone [20] and levosimendan [21] have been suggested, and some animal models do show possible pulmonary vasodilatation with milrinone [22] , but there is no clinical research data to support their use.…”
Section: Interventionmentioning
confidence: 99%
“…age, weight, peripartal asphyxia, renal failure) into account. Similarly, reported pharmacodynamic outcome measures were mixed (cliniIn this edition of Neonatology , two studies about levosimendan in low cardiac output states in an animal hypoxic-ischemic encephalopathy model and in 2 human neonates with persistent pulmonary hypertension (PPHN) are published [1,2] . Levosimendan is a Ca 2+ sensitizer with positive inotrope and lusitrope effects.…”
mentioning
confidence: 99%
“…Lusitrope effects occur by preventing diastolic calcium overload compared to other adrenergic agents so diastolic relaxation is improved without increased myocardial oxygen consumption. By opening ATP-sensitive potassium channels, vasodilation of the smooth muscles occurs with coronary vasodilation and decrease in systemic and pulmonary vascular resistance (PVR) [1][2][3] . These properties make this inotropic theoretically also useful in neonates.…”
mentioning
confidence: 99%
See 1 more Smart Citation